2015
DOI: 10.1002/ijop.12218
|View full text |Cite
|
Sign up to set email alerts
|

What is beautiful brings out what is good in you: The effect of facial attractiveness on individuals' honesty

Abstract: This study tested whether the presence of an attractive face would influence individuals' honesty. In 2 experiments, 225 participants were asked to predict the outcome of computerised coin-flips and to self-report the accuracy of their predictions. Self-reports were made in the presence of a facial photo of a female who had been rated before the experiment as high attractive, middle attractive or low attractive by other volunteers. Participants were rewarded based on their self-reported (not actual) accuracy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(41 reference statements)
0
8
0
2
Order By: Relevance
“…In addition, some studies have found that facial perception may be modulated by gender [ 22 , 25 , 42 44 ]. Ishai [ 45 ] found an interaction between the perceptions of facial attractiveness and the sexual preference of the participant: in heterosexual women and homosexual men, attractive male faces elicited stronger activation than attractive female faces, whereas in heterosexual men and homosexual women, attractive female faces evoked stronger activation than attractive male faces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some studies have found that facial perception may be modulated by gender [ 22 , 25 , 42 44 ]. Ishai [ 45 ] found an interaction between the perceptions of facial attractiveness and the sexual preference of the participant: in heterosexual women and homosexual men, attractive male faces elicited stronger activation than attractive female faces, whereas in heterosexual men and homosexual women, attractive female faces evoked stronger activation than attractive male faces.…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, more attractive children were found to have higher IQs (by 12.4 points) (Kanazawa, 2011). People in one study were found to be more honest and moral when they saw the face of a more attractive person (Wang et al, 2017). This suggests that people respond to and treat attractive people differently than others.…”
Section: Journal Of Young Investigatorsmentioning
confidence: 98%
“…Por ejemplo, la investigación en los efectos de los estímulos estéticos en la cognición moral ha encontrado que la percepción de rostros atractivos incrementó la honestidad de los participantes (Wang et al, 2015), un resultado congruente con la existencia implícita (pero ampliamente operativa) del estereotipo "si es bello es bueno" (Shannon y Shark, 2003).…”
Section: Evidencia Empírica Del Modelounclassified